Does the Motivation for Market‐Based Reform Matter? The Case of Responsibility‐Centered Management. (16th November 2017) - Rutherford, Amanda; Rabovsky, Thomas
Abstract: Organizational theorists have long examined the implications of market‐oriented policies for public agencies. Current research often aims to understand the effects of policies imposed on organizations by external stakeholder groups, but few studies have attempted to gain a better understanding of what mechanisms cause agencies to select into these strategies. The purpose of this article is to understand, first, which factors make an organization more likely to adopt a decentralized, market‐based budgeting system—termed "responsibility‐centered management (RCM)—and, second, whether this type of system has implications for organizational performance. Using data on doctorate‐granting public and private nonprofit four‐year universities in the United States, the authors find that mission, resource dependence, and state party control influence the take‐up of RCM. In terms of effects, RCM creates winners for graduation rates (white students) and degree production (science, technology, engineering, and math departments), which raises questions of equity across groups .